2007
DOI: 10.1002/mrd.20695
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of MAPK affects centrosome assembly, but not actin filament assembly, in mouse oocytes maturing in vitro

Abstract: Mitogen-activated protein kinase (MAPK) plays a crucial role in meiotic maturation of mouse oocytes. In order to understand the mechanism by which MAPK regulates meiotic maturation, we examined the effects of the MAPK pathway inhibitor U0126 on microtubule organization, gamma-tubulin and nuclear mitotic apparatus protein (NuMA) distribution, and actin filament assembly in mouse oocytes maturing in vitro. Western blotting with antibodies that detect active, phosphorylated MAPK revealed that MAPK was inactive in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…When MAPK3/MAPK1 activity was blocked by specific MEK1/2 inhibitor U0126 from the beginning of IVM, bovine oocytes progress through GVBD, but could not reach the correct MI stage (Tosca et al 2007); the same effect was reported in mice (Lee et al 2007). In contrast, when mouse oocytes were treated by U0126 after GVBD, although the phosphorylation of MAPK3/MAPK1 was drastically reduced, the polar body extrusion was normal, but the organisation of metaphase plate and chromosome segregation were affected (Lee et al 2007). Thus, in bovine oocytes, LiCl 2 led to the inhibition of MAPK3/MAPK1 activation prior to GVBD, which in turn contributed to the arrest at first meiotic division.…”
Section: Gsk3b Expression In Bovine Oocytes and Surrounding Folliculasupporting
confidence: 52%
“…When MAPK3/MAPK1 activity was blocked by specific MEK1/2 inhibitor U0126 from the beginning of IVM, bovine oocytes progress through GVBD, but could not reach the correct MI stage (Tosca et al 2007); the same effect was reported in mice (Lee et al 2007). In contrast, when mouse oocytes were treated by U0126 after GVBD, although the phosphorylation of MAPK3/MAPK1 was drastically reduced, the polar body extrusion was normal, but the organisation of metaphase plate and chromosome segregation were affected (Lee et al 2007). Thus, in bovine oocytes, LiCl 2 led to the inhibition of MAPK3/MAPK1 activation prior to GVBD, which in turn contributed to the arrest at first meiotic division.…”
Section: Gsk3b Expression In Bovine Oocytes and Surrounding Folliculasupporting
confidence: 52%
“…Higher levels of U0126 (10 mM) were required to prevent PBE when treatment was done after GVBD (data not shown). This phenomenon suggests that the differences in the reports of Tong et al, Lee et al and Yu et al might be dependent on the timing and concentration of U0126 treatment (Tong et al, 2003;Lee et al, 2000;Lee et al, 2007;Yu et al, 2007).…”
Section: Resultsmentioning
confidence: 83%
“…In contrast, Mos knockout (Mos-KO) mouse oocytes extrude abnormally big polar bodies and enter parthenogenesis (Choi et al, 1996;Verlhac et al 2000), but injection of Mos antisense oligonucleotides (MosAS) (Paules et al, 1989) at GV stage prevents PBE in wild-type mouse oocytes. Despite these differences, inhibition of MEK activity by U0126 at GV stage prevents PBE consistently in cnidarian, mouse and pig oocytes (Lee et al, 2000;Lee et al, 2007;Amiel et al, 2009). However, variable results were obtained about MEK inhibition following GVBD in mouse oocytes: extrusion of normal polar bodies, large polar bodies, polar bodies without chromosomes or no polar bodies (Tong et al, 2003;Lee et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following germinal vesicle breakdown (GVBD), the chromatin is condensed, the metaphase I (MI) spindle is organized and oocytes extrude the first polar body upon completion of meiosis I. Subsequently, oocytes develop to metaphase of meiosis II (MII) and maintain the second meiotic arrest until fertilization [1][2][3]. Protein phosphorylation and dephosphorylation play pivotal roles in the oocyte meiotic cell cycle.…”
mentioning
confidence: 99%